1982
DOI: 10.1143/jjap.21.l624
|View full text |Cite
|
Sign up to set email alerts
|

Ba(Mg1/3Ta2/3)O3 Ceramics with Temperature-Stable High Dielectric Constant and Low Microwave Loss

Abstract: A dense ceramic with an ordered perovskite structure with chemical formula Ba(Mg1/3Ta2/3)O3 is prepared, aiming at materials for a dielectric resonator with temperature-stable high dielectric contsant and low loss at microwave frequency. A small amount of Mn ion is doped to the sample to complete the sintering. The dielectric constant and unloaded Q are 25 and 16800 at 10.5 GHz respectively. The temperature coefficient of resonant frequency is estimated as 2.7 ppm/°C in the vicinity of room temperature. The va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(108 citation statements)
references
References 11 publications
0
108
0
Order By: Relevance
“…Single-phase MW dielectrics are produced on the basis of solid solutions [6,15,98] using heterovalent substitutions in one of the crystal sublattices and influencing thereby the phonon spectrum [10] and by making one of the sublattices "mobile" [151]. At the same time, high-Q thermostable MW dielectrics based on multiphase systems are developed using the volume temperature compensation effect [55-57, 124, 132, 135].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-phase MW dielectrics are produced on the basis of solid solutions [6,15,98] using heterovalent substitutions in one of the crystal sublattices and influencing thereby the phonon spectrum [10] and by making one of the sublattices "mobile" [151]. At the same time, high-Q thermostable MW dielectrics based on multiphase systems are developed using the volume temperature compensation effect [55-57, 124, 132, 135].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Nomura with coauthors [98] proposed to prepare dense ceramics ( ≈ 7520 kg/m 3 ) by using additionally manganese impurities. Matsumoto and Hinga [99] used fast heating (330 0 C/min) for the same purposes, which made it possible to achieve 96% of the theoretical density.…”
Section: Ba(m 2+mentioning
confidence: 99%
“…Ba(Mg 1 / 3 Τa2 /3)O3 (BMT), in particular, was reported to have a dielectric constant K ti 25 and dielectric Q 16, 800 (one of the highest in the oxide family) at 10.5 GHz, in samples with 1 mol% Mn additive as a sintering aid [5]. BMT compound is one of the most refractory oxides known thus the growth of single crystals is difficult.…”
Section: βA(μg1/3τa2/3)o3 (βμτ)mentioning
confidence: 99%
“…A number of dielectric ceramics based on complex perovskite compounds with the general formula A(B1/3B~/3)O3 (A = Ba, Sr; B = Mg, Zn, and Ni; and B' = Nb, Ta) have been investigated for this purpose [1][2][3][4][5], and the Ba(Mgl/3Ta2/3)O 3 (BMT) ceramics are of special interest due to their ultralow dielectric loss and the temperature independence of their dielectric constant [1,6]. However, BMT powders created by conventional solid-state-reaction methods have very poor sinterabilities [7], and this has been a serious problem in the practical applications of the present ceramics..…”
Section: Introductionmentioning
confidence: 99%
“…Nomura et al [1] created BMT ceramics with a bulk density of 7520 kg m -3 using Mn additives. Inuzuka et al [8] reported that BMT ceramics had a bulk density of 0.98 TD (theoretical density), but the value of used TD here was not stated by these authors; these values were obtained by adding P in amounts less than 1 wt %.…”
Section: Introductionmentioning
confidence: 99%